2016
DOI: 10.1038/srep37366
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of hereditary hemorrhagic telangiectasia generated by transmammary-delivered immunoblocking of BMP9 and BMP10

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a potentially life-threatening genetic vascular disorder caused by loss-of-function mutations in the genes encoding activin receptor-like kinase 1 (ALK1), endoglin, Smad4, and bone morphogenetic protein 9 (BMP9). Injections of mouse neonates with BMP9/10 blocking antibodies lead to HHT-like vascular defects in the postnatal retinal angiogenesis model. Mothers and their newborns share the same immunity through the transfer of maternal antibodies during lactation. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 74 publications
1
52
0
Order By: Relevance
“…Indeed, HHT-causing mutations decrease Smad1/5/8 response to ALK1-endoglin receptor activation by BMP9 (14)(15)(16). Consistent with this model, ALK1, endoglin, or Smad4 inactivation in mice and zebrafish leads to vascular defects, which include hypervascularization and AVMs (17)(18)(19)(20)(21)(22)(23)(24)(25). Downstream from ALK1-endoglin receptor loss-of-function, the exact pathways involved in HHT pathogenesis and ultimately, AVM development-i.e., the formation of direct shunts between an artery and a vein-remain incompletely understood (26).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed, HHT-causing mutations decrease Smad1/5/8 response to ALK1-endoglin receptor activation by BMP9 (14)(15)(16). Consistent with this model, ALK1, endoglin, or Smad4 inactivation in mice and zebrafish leads to vascular defects, which include hypervascularization and AVMs (17)(18)(19)(20)(21)(22)(23)(24)(25). Downstream from ALK1-endoglin receptor loss-of-function, the exact pathways involved in HHT pathogenesis and ultimately, AVM development-i.e., the formation of direct shunts between an artery and a vein-remain incompletely understood (26).…”
Section: Introductionmentioning
confidence: 76%
“…Recently, we have reported the development of a HHT mouse model, which uses the transmammary route for administering BMP9 and BMP10 blocking antibodies to nursing mouse pups (22,32), hereafter referred to as the transmammary-treated BMP9/10 immunoblocked (tBMP9/10ib) mice. We showed that this model, which has the advantage of being less invasive for the pups and more suitable for the analysis of large cohorts, leads to reduced ALK1 signaling and the development of a robust HHT-like pathology in the retinal vasculature of the pups (22,32). In this model, we found that Tac significantly activated endothelial ALK1 signaling in vivo and prevented hypervascularization of the tBMP9/10ib retina.…”
Section: Sirolimus and Nintedanib Combination Prevents Vein Dilationmentioning
confidence: 99%
“…However, the embryonic requirement for Bmp10 in the mouse vasculature has been attributed to the slightly earlier expression of Bmp10 (E8.5) compared to Bmp9 (E9.75–E10), which masks functional redundancy. In support of this hypothesis, insertion of Bmp9 into the Bmp10 locus allows Bmp9 to be expressed in the endogenous spatiotemporal pattern of Bmp10 and prevents embryonic AVMs [120], and combined postnatal immunodepletion of Bmp9 and Bmp10 is required for development of retinal vascular dysplasia and AVMs [61, 120, 121, 137]. However, replacement of Bmp10 with Bmp9 not only fails to rescue trabeculation defects, presumably because of a unique requirement for Bmp10 in inducing cardiomyocyte proliferation independent of Alk1 [138], but also results in dilated, leaky vasculature [120].…”
Section: Alk1 Signaling In Ecsmentioning
confidence: 99%
“…TMEM100 is induced by endoplasmic reticulum stress [177] and is localized to the plasma membrane [178], suggesting that it may be involved in chaperoning transmembrane receptors through the endomembrane system. Finally, angiopoietin 2 ( Angpt2 ), an autocrine-acting pro-angiogenic factor, is increased in mice and cultured ECs with disrupted Alk1 signaling [54, 137]. Whether any of these genes is directly regulated by pSMAD1/5/8 remains to be determined.…”
Section: Alk1 Signaling In Ecsmentioning
confidence: 99%
See 1 more Smart Citation